A 4D-Role Based Access Control Model for Multitenancy Cloud Platform. (28th February 2016) - Li, Jiangfeng; Liao, Zhenyu; Zhang, Chenxi; Shi, Yang
Abstract : Since more and more applications and services have been transferred from servers in the B/S architecture to cloud, user access control has become a significant part in a multitenancy cloud platform. Role based access control model makes users participate in an enterprise system as particular identities. However, in a multitenancy cloud environment, it has a high probability that the information of tenants has been leaked by using existing role based access control (RBAC) model. Moreover, management problems may emerge in the multitenancy platform with the increment of the number of tenants. In this paper, a novel concept of 4D-role is presented. With a detailed definition on the concept of 4D-role, a 4D-role based multitenancy model is proposed for running various applications and services in the multitenancy cloud platform. A theoretical analysis indicates that the model has the characters of tenant isolation, role hierarchy, and administration independence. The three characters are also verified by experimental evaluation. Moreover, the evaluation results indicate that the model has a good performance in using cloud resources when large-scale users are operating in the cloud platform simultaneously.